2016
DOI: 10.15386/cjmed-517
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic, Dermoscopic and Ultrasound Examination of a Rare Acral Tumour Involving the Nail- A Case Report and Review of the Literature

Abstract: There is a large spectrum of tumors presenting as nodular lesions that may affect the subungual space. We report the case of a 62-year-old woman presenting with a rapidly growing nodular lesion under the nail of the first left toe. Non-invasive examinations using dermoscopy, ultrasonography and elastography were performed for the preoperative assessment of the lesion. The biopsy of the lesion revealed superficial acral fibromyxoma, a benign tumor with predisposition for acral sites. The patient underwent radic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
1
8

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 13 publications
3
13
1
8
Order By: Relevance
“…The diagnosis is established by clinicopathological and immunohistochemical examination. In our case, the dermoscopic examination revealed a yellowish, hyperkeratotic, finger-like projection, a structureless homogeneous white area in the tumor, and linear vessels, which differs from the dermoscopic description reached in a study by Grigore [2].…”
Section: Letter To the Editorcontrasting
confidence: 99%
“…The diagnosis is established by clinicopathological and immunohistochemical examination. In our case, the dermoscopic examination revealed a yellowish, hyperkeratotic, finger-like projection, a structureless homogeneous white area in the tumor, and linear vessels, which differs from the dermoscopic description reached in a study by Grigore [2].…”
Section: Letter To the Editorcontrasting
confidence: 99%
“…It has a benign behavior; however, it may show persistance or recurrence if not treated properly . To date, 4 cases were reported with dermoscopic images in literature and our case is the fifth SAFM described with dermoscopic characteristics . Herein, we report a case of SAFM in the heel with a new finding on dermoscopy.…”
Section: Introductionmentioning
confidence: 75%
“…Aguado et al reported a white, scar‐like patch with shiny white streaks and small arborizing vessels with an in‐focus central telangiectasia . Grigore et al presented a structureless homogeneous red area within the tumor . Cullen et al showed a scar‐like patch with shiny white striae and small blood vessels arranged perpendicular to the surface .…”
Section: Discussionmentioning
confidence: 99%
“…Foram encontrados na literatura atual 314 casos descritos de FAS com localização variada, representados na tabela 1 . 1 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38…”
Section: Resultsunclassified
“…O tratamento desses tumores tipicamente envolve a excisão completa para excluir a malignidade e prevenir a recorrência, segundo dez trabalhos. 1 4 6 8 12 22 26 28 30 35…”
Section: Resultsunclassified